1999
DOI: 10.1016/s0022-2275(20)33385-x
|View full text |Cite
|
Sign up to set email alerts
|

A new 6-hydroxy-4-sphingenine-containing ceramide in human skin

Abstract: A new ceramide consisting of 6-hydroxysphingosine linked to a non-hydroxyacid was found in human epidermal lipid. This ceramide was sought because its fatty acid and sphingoid moieties are present in other combinations in human epidermal ceramides. To isolate the new ceramide, the mixture of ceramides in human epidermal lipid was first separated into fractions by thin-layer chromatography (TLC), and then each fraction was further purified by TLC after acetylation of all hydroxyl groups. TLC after acetylation r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
39
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 103 publications
(39 citation statements)
references
References 14 publications
0
39
0
Order By: Relevance
“…These observations suggested that they could be the different members of the family of 6oh-Sphes (3)(4)(5). Indeed, these compounds had two hydroxyl groups in an ␣-position relative to a double bound, a symmetrical situation that, relative to classical Sphes, theoretically increased the number of products provoked by the resonance of the carbonium ion between C (3) and C (5) formed during anhydrous acidcatalyzed methanolysis of Sphes up to five different compounds (Fig. 6).…”
Section: Heterogeneity Of 6oh-sphesmentioning
confidence: 97%
See 2 more Smart Citations
“…These observations suggested that they could be the different members of the family of 6oh-Sphes (3)(4)(5). Indeed, these compounds had two hydroxyl groups in an ␣-position relative to a double bound, a symmetrical situation that, relative to classical Sphes, theoretically increased the number of products provoked by the resonance of the carbonium ion between C (3) and C (5) formed during anhydrous acidcatalyzed methanolysis of Sphes up to five different compounds (Fig. 6).…”
Section: Heterogeneity Of 6oh-sphesmentioning
confidence: 97%
“…As previously reported (1,2,8,9), Sphes (1,3-dihydroxy-2-amino-4-ene-alkenes) gave three peaks upon acid-catalyzed anhydrous methanolysis. Indeed, these compounds form a carbonium ion in resonance between C (3) and C (5) . A subsequent nucleophilic attack by CH 3 O Ϫ at the 3 or 5 position gave a mixture of derivatives, already observed with conventional methods (8).…”
Section: Heterogeneity Of Sphesmentioning
confidence: 99%
See 1 more Smart Citation
“…This will help us understand the changes in barrier function and lipid organization in diseased and dry skin. In human SC at least eight subclasses of CER are present (20,21). These HCER, often referred to as HCER1 to HCER8, differ from each other in head group architecture and hydrocarbon chain length.…”
mentioning
confidence: 99%
“…6-Hydroxysphingosine is also found in three classes of free ceramides of human skin. The fatty acid moieties of these three classes are: nonhydroxyacids, ␣ -hydroxyacids, or -hydroxyacids having a nonhydroxyacid esterified to the -hydroxyl group (12,13).…”
Section: Structure Of the Corneocyte Lipid Envelopementioning
confidence: 99%